Sportfähigkeit nach Schulterarthroplastik - Schmidt-Wiethoff, R.; Wolf, P.; Lehmann, M.; Habermeyer, P. (Sportverletzung Sportschaden, 2002)
A hemi- or total shoulder arthroplasty was performed in 171 patients between 1992 and 1997. We examined 118 patients under the age of 70 regarding their level of physical activity. For a pre- and postoperative comparison we divided the patients in two groups. Group one included all patients with osteoarthritis, rheumatoid arthritis, instability associated arthritis, avascular necrosis and other arthropathies. Group two included acute fractures and fracture sequelae. The postoperative outcome was functionally assessed by using the Constant score. There was an average Constant score of 60,9 for group one and 67,1 for group two. Both groups showed a domination of activities with motion patterns unspecific for the shoulder. There were more patients in group two reporting activities which depend on a good or very good shoulder function. There is no general estimation for the ability to be active in sports after shoulder arthroplasty. An individual assessment of the shoulder function is essential. Important criterias beside motivation and age are the status of the rotator cuff and the soft tissue balancing. The correct indication for shoulder arthroplasty as well as the preoperative planning and the postoperative rehabilitation program are essential for a good functional outcome and the key for physical activity after shoulder arthroplasty.